Chronic Epstein-Barr viral load carriage after pediatric organ transplantation - Yamada, Masaki; Chen, Sharon F.; Green, Michael (Frontiers in Pediatrics, 2024)
Epstein-Barr virus (EBV) infection and EBV-associated post-transplant lymphoproliferative disorder (EBV/PTLD) is one of the most devastating complications occurring in pediatric solid organ transplant (SOT) recipients. Observations of SOT recipients undergoing serial EBV monitoring to inform reduction of immune suppression to prevent EBV-/PTLD has identified patients who maintain chronic high EBV load (CHL) in their blood. The CHL carrier state has been seen more commonly in pediatric compared to adult transplant recipients. Some but not all CHL may progress to EBV/PTLD. However, little is known regarding the biology of this CHL carrier state and the optimal clinical approach to CHL has not been established. This review summarizes the current knowledge and evidence of chronic high EBV load and introduces commonly adopted approaches from experts in this field.